Primetime TV program preference of the residents of Las Pinas Metro Manila an audience profile - Agcaoili, Ma. Christina A.
This survey-research was conducted to be able to get a general consensus among the residents of the Municipality of Las Pinas Metro Manila regarding their general program type preference during primetime hours. Another objective of the study was to compare the general program preference of male and female audiences. A correlated study between sex and preference was also incorporated. The design used in the study was the modified one-shot case study design. Questionnaires were given to 100 respondents, equally distributed among 50 males and 50 females. Random clusters were selected in each barangay, with immediate family members given preference. Primetime program types were obtained by listing down the 12 different program types aired during primetime hours. Preference was measures through getting the five most preferred types from among the 12 program types aired during primetime hours. The study revealed that the five most preferred program types of the residents of Las Pinas were: comedy shows, newscasts, detective/action shows, foreign movies and sports, in that order. Male preferences differed somewhat from the female preferences in that the order of preferred programs were: detective/action shows, sports, comedy shows, newscasts and foreign movies. Female audiences preferred comedy shows first, then foreign movies, musical/variety shows, newscasts and talkshows.